New records of Coccomyces (Rhytismatales, Ascomycota) for Mexico - Valenzuela, Ricardo; Raymundo, Tania (Instituto de Ecología, A.C., 2018)
Background and Aims: Coccomyces presents subcircular to polygonal ascomata, which are immersed in leaves with black stroma, leaving upon maturity the hymenium exposed and eruptive. The asci are subclavate to cilindrical, and filiform paraphyses with uncinated, coiled, swollen, lanceolated apices. The ascospores are subclavate to filiform and surrounded by a mucilaginous sheath. This genus is endophytic, better known as foliicolous fungi, by forming fructifications on leaf litter in temperate regions. About 116 species have been described. In Mexico, only Coccomyces arctostaphyloides and C. parasiticus have been registered. The main objective of this study is to contribute to the taxonomic knowledge of the genus in the cloud forests from the states of Hidalgo and Puebla, Mexico.Methods: The material deposited in the collection of fungi of the ENCB herbarium was revised, and fresh specimens were collected in the municipalities Zacualtipán de Ángeles and Acaxochitlán, Hidalgo, and those of Honey and Naupan, Puebla. The species were determined and described morphologically, following the traditional mycological techniques.Key results: Coccomyces coronatus and C. tumidus (Rhytismataceae) are registered for the first time for Mexico. The first one is characterized by polygonal apothecia immersed in leaves of Fagus mexicana in the municipality Zacualtipan de Ángeles, Hidalgo, and leaves of Quercus sp. in that of Honey, Puebla, while the second species forms superficial and circular apothecia on leaves of Quercus ilex in the municipalities Acaxochitlán, Hidalgo and Naupan, Puebla. Taxonomic descriptions and illustrations of both foliicolous species from the cloud forest are presented.Conclusions: The endophytic and foliicolous fungi of the Rhytismataceae family are poorly known in Mexico; hence, it is necessary to continue explorations and taxonomic studies that will enrich the knowledge of these fungi in the country.